Dependence and Perceived Difficulty in Daily Activities in Community-Living Stroke Survivors 2 Years After Stroke: A Study of Instrumental Structures - Grimby, Gunnar; Andrén, Eva; Daving, Yvonne; Wright, Benjamin (Stroke (1970), 1998)
Background and Purpose —There is a need for better understanding of the structure of instruments for functional outcome assessment after discharge from rehabilitation. One purpose of the study was to contribute to the analysis of instrumental dimensionality. Another purpose was to compare disability in stroke patients within the younger age range 2 years after onset of stroke with that at discharge with respect to both dependence and patients’ perceived difficulty and to extend the assessments with instrumental activities. Methods —We studied 68 stroke survivors aged 18 to 71 years at onset (59% aged <55 years) by means of interviews in their home, using activities from the Functional Independence Measure (FIM) and Instrumental Activity Measure (IAM) for ratings of dependence and perceived difficulty. Rasch analysis was used to construct calibrated linear measures and to evaluate the level of fit. Results —Acceptable models for comparison of dependence between discharge and follow-up were found for the physical and the social-cognitive items in FIM. However, personal care and social-cognitive items showed an increased level of dependence at follow-up compared with at discharge. A combination of physical activities from FIM and IAM also gave acceptable models for both dependence and perceived difficulty, and the hierarchical orders of activities are presented. In general, there was agreement between the ratings of dependence and perceived difficulty, but with some discrepancies. Men found it harder to be independent in such instrumental activities as cooking and cleaning than women; the opposite was true for small-scale shopping and locomotion outdoors. Subjects aged ≥55 years had slightly higher level of dependence and perceived difficulty in IAM activities than those below that age. Conclusions —Changes in the hierarchical order of activities should be taken into account in follow-up studies. Differences in the environment between hospital and home, as well as differences in support and motivation, might explain the relatively larger degree of dependence at follow-up compared with at discharge and indicate the need for further rehabilitation efforts. Instrumental activities could be combined with FIM activities in a model. For individual items, ratings of both dependence and perceived difficulty may provide further insight into the disablement process.